2009
DOI: 10.1007/s10162-009-0194-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hearing Preservation on Psychophysical Responses to Cochlear Implant Stimulation

Abstract: Previous studies have shown that residual acoustic hearing supplements cochlear implant function to improve speech recognition in noise as well as perception of music. The current study had two primary objectives. First, we sought to determine how cochlear implantation and electrical stimulation over a time period of 14 to 21 months influence cochlear structures such as hair cells and spiral ganglion neurons. Second, we sought to investigate whether the structures that provide acoustic hearing also affect the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
84
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(100 citation statements)
references
References 59 publications
16
84
0
Order By: Relevance
“…For multipulse integration, the animal studies have demonstrated that a significant amount of the variance in the slopes of the functions could be accounted for by the density of the spiral ganglion cell bodies of the auditory neurons in Rosenthal's canal near the stimulation sites (Kang et al, 2010;Pfingst et al, 2011b). The mechanism for the effects of auditory fiber density on the ear's ability to integrate multiple electrical pulses is not fully understood.…”
Section: A Across-site Variationmentioning
confidence: 99%
See 3 more Smart Citations
“…For multipulse integration, the animal studies have demonstrated that a significant amount of the variance in the slopes of the functions could be accounted for by the density of the spiral ganglion cell bodies of the auditory neurons in Rosenthal's canal near the stimulation sites (Kang et al, 2010;Pfingst et al, 2011b). The mechanism for the effects of auditory fiber density on the ear's ability to integrate multiple electrical pulses is not fully understood.…”
Section: A Across-site Variationmentioning
confidence: 99%
“…In McKay and colleagues' model of temporal processing (McKay and McDermott, 1998;McKay et al, 2013), detection of pulsatile stimulation in electric hearing is influenced by a combined effect of reduced neural response due to refractory effects and temporal integration of neural activity in the integration window. Previous reports have shown that guinea pigs with sparse neural survival also tend to have low spontaneous activity in the remaining fibers, probably due to the loss of inner hair cells (Kang et al, 2010;Pfingst et al, 2011b). The lack of spontaneous activity can lead to abnormal across-fiber synchrony.…”
Section: A Across-site Variationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, previous studies have shown that the relationship between survival of hair cells and auditory neurons and psychophysical detection thresholds depends on the parameters of stimulation (Su et al, 2008;Kang et al, 2010). The relationship is positive for some types of stimuli and negative for others.…”
Section: Introductionmentioning
confidence: 97%